The Ancient Army against Dangerous Animals in the "Pantheon of Sandomierz" - Ptak, Jan (Armia kontra natura, 2020)
In the medieval manuscript, called the Pantheon of Sandomierz, together with Godfred’s work from Viterbo, there is an apocryphal letter from Alexander the Great to Aristotle. In it, the Macedonian king describes the adventures he experienced with his army during his expedition to India. A large part of them are the battles he had to fight together with his people with the dangerous animals he met there, attacking them during this journey. These included hippos, lions, snakes, boars, big mice, bats, scorpions, crayfish, elephants, and monstrous creatures, one of which had two heads, the other had three horns on its head, and the other had sharp, toothed bones protruding from its forehead. To resist their attacks, they required different ways and the use of weapons that Macedonian soldiers were equipped with. The descriptions of these struggles are illustrated by colored drawings in the manuscript. The king and his subordinates were depicted on them in accordance with the fourteenth century realities, while the appearance of the animals is an effect of the draftsman’s imagination. The ideal content of this work is consistent with the principles of the medieval knightly ethos, which preached the need to face the forces of evil, symbolically embodied also by dangerous animals.